Management Control Systems – Strategic Alignment Relations: A Study at Itaipu Binacional - Ronaldo Tavares; Wenderson Diego Norberto; Eloi Damke; Luciano Panek (BBR: Brazilian Business Review)
Several papers have connected management controls to strategic commitment, innovation, and corporate governance, among other organizational outcomes. There are few studies that relate the levers of control framework proposed by Simons (1995) to strategic alignment. This paper aims to evaluate the relationships between Simons´ strategic levers of control with the vertical strategic alignment at Itaipu Binacional. Data collected through a survey of 341 respondents and analysed through structural equation modelling by the Partial Least Squares (PLS) method revealed that the levers of control are associated, exerting a positive influence, with the strategic alignment, with diagnostic, beliefs, and interactive systems showing significant statistical associations.